2003
DOI: 10.1074/jbc.m212918200
|View full text |Cite
|
Sign up to set email alerts
|

Truncation of the A1 Adenosine Receptor Reveals Distinct Roles of the Membrane-proximal Carboxyl Terminus in Receptor Folding and G Protein Coupling

Abstract: The carboxyl terminus (C-tail) of G protein-coupled receptors is divergent in length and structure and may represent an individualized cytoplasmic domain. By progressively truncating the A 1 adenosine receptor, a G i/o -coupled receptor with short cytoplasmic stretches, we identify two inherent functions of the C-tail, namely a role in receptor export from the endoplasmic reticulum (ER) and a role in G protein coupling. Deletion of the last 22 and 26 amino acids (of 36) reduced and completely abolished surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
54
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 64 publications
7
54
0
Order By: Relevance
“…Similar findings, i.e. a reduced functionality and retention in the ER, have been demonstrated for other GPCRs with a truncated membrane-proximal, intracellular C terminus, such as the luteinizing hormone/chorionic gonadotropin receptor (21), the vasopression 2 receptor (22), and the A1 adenosine receptor (23). This indicates that the cellular signaling response is determined by the amount of functionally active receptor in the plasma membrane (PM) (24).…”
Section: Tgr5 (Gpbar-1 M-bar) Is a G Protein-coupled Receptor (Gpcr)supporting
confidence: 48%
“…Similar findings, i.e. a reduced functionality and retention in the ER, have been demonstrated for other GPCRs with a truncated membrane-proximal, intracellular C terminus, such as the luteinizing hormone/chorionic gonadotropin receptor (21), the vasopression 2 receptor (22), and the A1 adenosine receptor (23). This indicates that the cellular signaling response is determined by the amount of functionally active receptor in the plasma membrane (PM) (24).…”
Section: Tgr5 (Gpbar-1 M-bar) Is a G Protein-coupled Receptor (Gpcr)supporting
confidence: 48%
“…These studies showed that the short cytosolic C-terminal tail of both receptors plays a crucial role in their targeting. As also reported for other GPCRs (Bermak et al, 2001;Duvernay et al, 2004;Oksche et al, 1998;Pankevych et al, 2003;Rodriguez et al, 1992;Tai et al, 1999), this region appeared to be necessary for the transport of 5-HT 1A R and 5-HT 1B R to the cell surface, because truncated receptors without the C-terminal domain were sequestrated within the endoplasmic reticulum (ER) in LLC-PK1 cells. Furthermore, these studies also demonstrated that the cytosolic C-terminal tail of 5-HT 1B R contains an axonal-apical targeting signal (Jolimay et al, 2000).…”
Section: Introductionmentioning
confidence: 68%
“…The requirement of the membrane-proximal C-terminal portion for ER export has been described for a number of GPCRs, including AT1R, ␣ 2B -AR, rhodopsin, vasopressin V2 receptor, dopamine D1 receptor, adenosine A1 receptor, melanin-concentrating hormone receptor 1, and luteinizing hormone/choriogonadotropin receptor (24,53,54). Mutagenesis studies have also identified a number of highly conserved motifs in the membrane-proximal C termini essential for GPCR export from the ER, such as the E(x) 3 LL, FN(x) 2 LL(x) 3 L, and F(x) 3 F(x) 3 F motifs (22,26,27).…”
Section: Discussionmentioning
confidence: 99%